The peculiarities of particles transition through split separatrix - Buts, V.A.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2005)
The dynamics of charged particle transition through a stochastic layer generated by a split separatrix is investigated on an example of mathematical pendulum motion with damping under acting of external periodic disturbance. It is shown that such layer has properties of an effective potential barrier, which can prevent to transition of charged particles through it. The dwelling time of particle in such layer can be anomalous large.